Mobile Application: Centralized Platform for Road Maintenance Issues - Amaradev , H.; Thilakaratne, P. (NSBM Green University, 2021)
My city is consisting of a mobile application and a web application. From this system, people can report road maintenance issues. A huge problem regarding road maintenance can be seen in every area in Sri Lanka. The purpose of this study is to develop a centralized platform to report road maintenance issues and reduce road traffic and maintain the standard of roads in Sri Lanka. So, to know the real situation of this problem the survey which is done to was very helpful. By the survey analysis, the likelihood of having this application and the desire of of having this kind of application was shown by the feedback. The mobile application provides the facility to retrieve the nearby issues based on their postal address, report issues and upload photos. The web application provides the facility to report the related issues to UC and the issues are shown to the UC and the RDA. After that, the RDA can assign the work by status of the work that has been assigned. RDA workers can get the information of the assigned work and report the status of the work assigned. These are the main facilities that are provided by this application
Keywords: Road Maintenance; Issues; Centralized platform; Mobile application; Web application